Determinants Of The Use Of Special Purpose Companies (SPCs) On Pre- And Post-IFRS: Empirical Evidence From Korea - Kim, Su-In; Shin, Heejeong; Shin, Hyejeong (Journal of Applied Business Research, 2017)
We investigate which factors determine the use of a special purpose company (SPC) by a sponsoring company and whether those determinants differ before and after IFRS (International Financial Reporting Standards) adoption. Using financial data from Korean listed companies, our results indicate that use of an SPC is associated with financial reporting incentives (e.g., lowering leverage) and economic benefits (e.g., fundraising). However, the effect of leverage on the use of SPCs is not significant after the adoption of the IFRS. These results suggest that, although companies are generally motivated to use SPCs for both financial reporting and economic purposes, only economic motivation influences the use of SPCs after IFRS adoption. This implies that the regulation for reporting an SPC’s consolidated financial statement under IFRS plays a role in decreasing the use of SPCs for financial reporting discretion. We extend the prior literature on SPCs by documenting the effects of IFRS adoption on the determinants of the use of SPCs.